1983
DOI: 10.1007/bf00255760
|View full text |Cite
|
Sign up to set email alerts
|

Decreased plasma half-life of cyclophosphamide during repeated high-dose administration

Abstract: Cyclophosphamide was given as IV doses of 50 mg/kg/day on each of four successive days as treatment for ovarian and lung cancer. Blood samples were taken at regular intervals and analysed for cyclophosphamide by gas liquid chromatography. The plasma half-lives (t 1/2) and volumes of distribution (V D) were calculated for each of the treatment days; t 1/2 was found to decrease with subsequent doses whereas V D was not significantly changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 6 publications
5
18
0
Order By: Relevance
“…The terminal elimination half-life of ifosfamide at this dose was similar to that for low dose cyclophosphamide (5.1 h) (Graham et al, 1983). The plasma decay of unchanged ifosfamide at this dose was best fitted by a monoexponential function, as shown by others (Creaven et al, 1976;Nelson et al, 1976 Our findings are similar to that of Lind et al (1989) using 1.5 g m2 ifosfamide intravenously daily for 5 days who found an increase in ifosfamide clearance from a median of 69.19 ml min -1 on day 1 to a median of 123.19 ml min -1 on day 5 without a change in ifosfamide distribution.…”
supporting
confidence: 59%
“…The terminal elimination half-life of ifosfamide at this dose was similar to that for low dose cyclophosphamide (5.1 h) (Graham et al, 1983). The plasma decay of unchanged ifosfamide at this dose was best fitted by a monoexponential function, as shown by others (Creaven et al, 1976;Nelson et al, 1976 Our findings are similar to that of Lind et al (1989) using 1.5 g m2 ifosfamide intravenously daily for 5 days who found an increase in ifosfamide clearance from a median of 69.19 ml min -1 on day 1 to a median of 123.19 ml min -1 on day 5 without a change in ifosfamide distribution.…”
supporting
confidence: 59%
“…The lower values of CY concentrations and the half-lives on the second day of treatment are due to the self-induction of CY metabolism as already described. [12][13][14][15] In conclusion, hemodialysis might be useful in removing metabolites of cyclophosphamide in patients with renal dysfunction receiving high-dose chemotherapy. 16 This report indicates that patients with severe renal failure may receive intensive myeloablative therapy with unrelated BMT without major adverse clinical events.…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that plasma half-life of cyclo in patients decreased both during repeated high dose administration (50 mg kg-I day-I for 4 successive days) and under continual low dose treatment of cyclo (100mg day-1 for over 1 year) (D'Incalci et al, 1979;Graham et al, 1983). One possible mechanism is that multiple doses of cyclo have an inducing effect on enzymes involved in the metabolism of cyclo, although in another clinical study, no change in cyclo metabolism was found in patients after 22 days of treatment with daily doses of 2mgkg-1 (Mouridsen et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In three clinical studies, the plasma half-life of cyclophosphamide decreased both after repeated low-dose and high-dose treatments (D'Incalci et al, 1979;Graham et al, 1983;Sladek et al, 1984). This was probably due to cyclophosphamide having an inducing effect on enzymes responsible for its metabolism, leading to an increased rate of disappearance of its metabolites from plasma.…”
mentioning
confidence: 99%